Variability in the Chemical Compositions of the Essential Oils of Five Ocimum Species from Tropical African Area - Tchoumbougnang, F; Zollo, Amwan P. H.; AVLESSI, FÉLICIEN; ALITONOU, GUY ALAIN; SOHOUNHLOUE, KOKO CODJO DOMINIQUE; Ouamba, Jean Mauril; Tsomambet, A; Okemy-Andissa, N; Dagne, E; Agnaniet, Huguette; Bessière, Jean Marie; MENUT, Chantal (My University, 2006)
As part of our research on aromatic plants from Africa, we have analyzed, via GC and CG/MS, the essential oils from fresh leaves of five Ocimum species from tropical Africa: Ocimum basilicum L., O. gratissimum L., O. americanum L. (syn: O. canum Sims), O. lamiifolium Hochst. ex Benth. and O. minimum L. The chemical compositions of O. basilicum, O. gratissimum and O. minimum essential oils could be related to some chemotypes already defined for these three species: linalool- or methyl chavicol-types for the first species, thymol- or eugenol- or ocimenes/far- nesenes-types for the second one; finally, a high content of methyl chavicol (34.3%) and linalool (17.8%) was found in O. minimum oil, similar to that already described for a Brazilian species. On the other hand, an essential oil dominated by 1,8-cineole was described for the first time for a sample of O. americanum. Finally, the oil of O. lamiifolium, which was rich in sabinene, is chemically described for the first time.
Keywords: Ocimum basilicum; Ocimum gratissimum; Ocimum americanum (Ocimum canum); Ocimum lamiifolium; Ocimum minimum; essential oil composition; 1; 8-cineole; linalool; thymol; methyl chavicol; sabinene; eugenol; (E; E)-α-farnesene; (Z)-β-ocimene